2011
DOI: 10.1193/1.3574445
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Scenario for Widespread Use: Best Practices, Lessons Learned

Abstract: The ShakeOut Scenario is probably the most widely known and used earthquake scenario created to date. Much of the credit for its widespread dissemination and application lies with scenario development criteria that focused on the needs and involvement of end users and with a suite of products that tailored communication of the results to varied end users, who ranged from emergency managers to the general public, from corporations to grassroots organizations. Products were most effective when they were highly v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…We reviewed abstracts of papers published in and after 2000 in the journals Natural Hazards Review and Earthquake Spectra and identified articles that presented the experience and concerns of end-users. These studies investigate end-users via interviews and participatory studies, or by presenting frameworks for tools and usability testing [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Research Articles: Emergency Management Andmentioning
confidence: 99%
“…We reviewed abstracts of papers published in and after 2000 in the journals Natural Hazards Review and Earthquake Spectra and identified articles that presented the experience and concerns of end-users. These studies investigate end-users via interviews and participatory studies, or by presenting frameworks for tools and usability testing [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Research Articles: Emergency Management Andmentioning
confidence: 99%
“…In addition to the drill, a range of communication initiatives were launched in the months leading up to it to raise public awareness about the drill and earthquake preparedness in general. For instance, there was a dedicated website where participants could access the following items: a narrative booklet, video and audio recording describing a 7.8 earthquake scenario linked to California’s San Andreas fault [ 13 , 14 , 15 ]; a drill manual that included information about developing an organizational and household disaster plan; graphic materials that could be printed to promote participation in the drill; and links to two educational video games called Beat the Quake and After Shock. Other initiatives included the development of ShakeOut groups on social media websites, community outreach meetings, and a two-day tabletop exercise.…”
Section: Introductionmentioning
confidence: 99%
“…These interpersonal activities aimed to enhance community engagement in disaster preparedness, drawing on the notion that shifts in social norms accompany changes at the individual level. Advertisements for the drill were additionally disseminated via broadcast radio as well as posters, billboards and electronic billboards displayed throughout the Los Angeles metropolitan area [ 13 , 14 ]. The “drop, cover and hold” message of these advertisements utilized a prescriptive approach for earthquake preparedness that aimed to elicit a very specific set of behaviors.…”
Section: Introductionmentioning
confidence: 99%